PENINGKATAN PENGUASAAN KOSA KATA UNGGAH-UNGGUH RAGAM KRAMA MELALUI MEDIA TEKA-TEKI SILANG BERBANTUAN CROSSWORD PUZZLE GAME PADA PESERTA DIDIK KELAS VIIIA SMP NEGERI 1 WELERI KENDAL SEMESTER 2 TAHUN PELAJARAN 2013/2014 - Romdonah . (Sasindo : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
Less of education participants class VIIIA Junior High School 1 Weleri Kendallearning year 2013/2014 on unggah-ungguh matter krama kinds can be solved by usinginovatif media. One of those is crossword media helped crossword puzzle game. Thisresearch by use two stap (cyklus I and cyklus II) that almed for knowing the intcreasingof krama?óÔé¼Ôäós kinds of unggah-ungguh vocabulary mastered and for knowing learningbehaviour change of education participants of class VIIIA Junior High School 1 WeleriKendal after the using crossword media helped crossword puzzle game. Mark on the17class of pracyclus the avarege mark of test result reach 68.00. That in increase 8.14 %on first cyclus with everage mark 76.14. Still 12 education participants 41,38% thatreach KKM yet. Test result on second cyclus increase 37.70% with clasikal averegemark 82.2. The increasing followed by changing learning attitude learning side.Keyword: mastered vocabulary, krama?óÔé¼Ôäós kinds unggah-ungguh, crossword helpedcrossword puzzle game.